A social‐aware probabilistic routing approach for mobile opportunistic social networks. Issue 12 (10th September 2017) - Zhao, Ruonan; Wang, Xiaoming; Zhang, Lichen; Lin, Yaguang
Abstract: In mobile opportunistic social networks (MOSNs), mobile users move around and conduct message transmission by using their portable devices without the support of communication infrastructures, in which routing is a challenge due to high connection intermittency and node mobility. The current routing schemes for MOSNs only focus on the improvement of cost‐effective delivery by using the characteristics of users' interests or mobility. In this paper, we propose a novel routing approach for MOSNs in which the probabilistic and social‐aware strategies are combined and the multiple‐copy policy is adopted. We first model an MOSN into some overlapping regions and then propose 2 region‐related centrality degrees related to users' social characteristics with the consideration of users' centrality, mobility, and interactions among users. According to the definition of centrality degrees, we design a social‐aware probabilistic routing approach in which a message replica control policy is applied to allow a user with higher encounter probability to the destination and the user could obtain more message replicas. The simulation results show that the proposed approach outperforms the previous routing algorithms in terms of delivery ratio and overhead ratio. Abstract : In this paper, a novel routing approach is proposed. We model an MOSN into some overlapping regions, and propose two region‐related centrality degrees related to users' social characteristics with the consideration of users' centrality, mobility and the interactions among users. We then design a social‐aware probabilistic routing (SAPR) approach, in which a message replica control policy is applied to allow a user with higher encounter probability to the destination could obtain more message replicas.